2001
DOI: 10.1007/s004410100371
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that a copper-metallothionein complex is responsible for fluorescence in acid-secreting cells of the Drosophila stomach

Abstract: Copper cells were originally identified in Drosophila midgut epithelium by their striking orange fluorescence in copper-fed larvae. Here, we examined copper cell fluorescence in light of the previous observations that (1) a similar fluorescent signal in yeast is produced by a complex between copper and metallothionein, and (2) metallothionein is expressed constitutively in the copper cell region and inducibly in other regions of the Drosophila midgut. Pulse-feeding experiments with 1 mM CuCl2 revealed that flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 29 publications
3
44
1
Order By: Relevance
“…Our finding that ferritin expression in the iron region is constitutive (and remains so even under iron-deficient conditions), but is inducible in the anterior midgut, has a parallel with the expression of metallothioneins, which are the copper storage proteins (Egli et al 2006). Interestingly, cuprophilic cells that are present anterior to the iron region show constitutive metallothionein expression (Mcnulty et al 2001), whereas cells in both the anterior and posterior midgut induce metallothionein expression and copper/metallothionein fluorescence at higher copper concentrations (Poulson and Bowen 1952;Mcnulty et al 2001) (Figure 5J). Results presented in this article, combined with previous reports, lead to the following fundamental conclusion with respect to metal metabolism in the midgut of Drosophila: the insect midgut contains two sets of specialized cells, one of which constitutively expresses metallothionein and a second constitutively expresses ferritin.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Our finding that ferritin expression in the iron region is constitutive (and remains so even under iron-deficient conditions), but is inducible in the anterior midgut, has a parallel with the expression of metallothioneins, which are the copper storage proteins (Egli et al 2006). Interestingly, cuprophilic cells that are present anterior to the iron region show constitutive metallothionein expression (Mcnulty et al 2001), whereas cells in both the anterior and posterior midgut induce metallothionein expression and copper/metallothionein fluorescence at higher copper concentrations (Poulson and Bowen 1952;Mcnulty et al 2001) (Figure 5J). Results presented in this article, combined with previous reports, lead to the following fundamental conclusion with respect to metal metabolism in the midgut of Drosophila: the insect midgut contains two sets of specialized cells, one of which constitutively expresses metallothionein and a second constitutively expresses ferritin.…”
Section: Discussionmentioning
confidence: 62%
“…(I) Cumetallothionein fluorescence (orange, asterisks) is prominent in the posterior midgut. (J) Cu-metallothionein fluorescence is also found in a cluster of cells anterior to the iron region, where constitutive metallothionein expression has been reported (Mcnulty et al 2001). (K and L) Time course of iron-dependent ferritin induction in (K) anterior midgut and (L) middle midgut dissected from third instar larvae.…”
Section: G188mentioning
confidence: 96%
See 1 more Smart Citation
“…Copper cells are the principal site of acid secretion in the midgut, and, like the Malpighian tubules, are thought to transport protons via apically localized V-type H + -ATPases (Dubreuil, 2004;Shanbhag and Tripathi, 2005). While a clear relationship between H + -ATPase output and copper uptake has yet to be elucidated, it has been shown that copper uptake is impaired in flies whose copper cells are deficient in acid secretion, and that the copper cell midgut region is less acidic following copper feeding (Dubreuil, 2004;McNulty et al, 2001). Similar to our proposed model in the Malpighian tubules, pHCl-2 may influence ATPase output in copper cells by regulating chloride counter-ion availability, which, in turn, could affect the rate of copper uptake.…”
Section: Discussionmentioning
confidence: 99%
“…The middle midgut, notably the copper-cell region, is devoted to the absorption of these metals (63,118). This region is stained by Prussian blue because of the presence of iron and becomes bright luminescent orange upon www.annualreviews.org • The Digestive Tract of Drosophila melanogastercopper ingestion as a result of the fixation of copper by metallothionein (58,111).…”
Section: Incorporation Of Metalsmentioning
confidence: 99%